Multiplicative relations among special points of modular and Shimura curves - Fowler, G (2021)
We consider a number of Diophantine problems for (mixed) Shimura varieties. Specifically, we look at the multiplicative relations satisfied by special points of modular and Shimura curves. These problems are closely related to the André--Oort and Zilber--Pink conjectures, and we will resolve some special cases of these conjectures.